Design and synthesis of novel quinazolinone derivatives as broad spectrum anticonvulsants - Ilangovan, P.; Ganguly, S.; Pandi, P.V.; Stables, J.P. (2010)
The present work was carried out to synthesize a series of substituted quinazolinone semicarbazones at third position of the quinazoline nucleus and chemically modifying second position of quinazolinone to get the compounds with lesser side effects and more potent anticonvulsive agents. Although several new anticonvulsants are already in clinical use, some types of seizures are still not adequately treated with current therapy and have limitations, intolerable side effects. In response to these limitations, the development of new drugs to optimally manage seizures has been strongly advocated. Thus the search for new anticonvulsant drugs continues to be an active area of investigation in medicinal chemistry. The present study describes the synthesis of newer quinazolinone derivatives and their anticonvulsant activities. The newly synthesized compounds were evaluated intraperitoneally into the mice in the maximal electro shock (MES), subcutaneous strychnine threshold test (scSTY), using doses 30, 100, 300 mg/kg, and neurotoxicity screens, observation was carried out at two different time intervals. Almost all the synthesized analogues were equipotent to phenytoin with very low neurotoxicity profile.